Epidemiological and etiological profile of the causes of hospitalization for meningitis in Cascavel- PR from 2017 to 2021 (Research, Society and Development, 2023)
Since meningitis is a desease of compulsory notification and epidemiologial importance due to its infective capacity, it’s important to draw a local epidemiological profile to understand the most prevalente etiologies and populations at risk. Objective: The epidemiological profile of residents in the city of Cascavel-PR affected by meningitis from 2017 to 2021 was evaluated, obtaining data: age, sex, race, antecedent diseases, history of contact, etiology, clinical manifestations, aspect of the cerebrospinal fluid, confirmation criteria and clinical outcome. These variables were compared with each other and national data in order to establish an overview of the disease in the city capable of guiding health actions. Methods: The study covered the patients residing in Cascavel-PR with a confirmed diagnosis of meningitis. Data was collected secondarily through SINAN, in the Epidemiological Surveillance. Results: Of the 247 patients, 59.92% were male and 40.08% were female. The most affected race was white. The age group from 1 to 19 years old was the most affected. The most prevalent etiology was viral meningitis (51.42%), followed by meningitis by other bacteria. The most used confirmation methods were CSF chemocytology and PCR. Most patients did not report contact with infected people. Conclusion: The present study found epidemiological characteristics similar to national studies in terms of sex and age. It concluded that the most common etiologies in Cascavel-PR were consistent with national findings. It also reaffirmed the importance of using proper diagnosis methods, avoiding underreporting and increasing the direction of the correct treatment, avoiding expenses with inappropriate therapy.